Development of molecularly imprinted polymeric nanofibers by electrospinning and applications to pesticide adsorption. Issue 8 (14th March 2015) - Ruggieri, F.; D'Archivio, A. A.; Di Camillo, D.; Lozzi, L.; Maggi, M. A.; Mercorio, R.; Santucci, S.
Abstract : Novel polystyrene‐based molecularly imprinted polymer nanofibers were synthesized through the electrospinning technique. The molecularly imprinted polymers were prepared using a non‐covalent approach and atrazine as template. For comparison, nonimprinted polymer nanofibers were also synthesized. The morphology of the synthesized nanofibers was characterized using scanning electron microscopy. The adsorption of pesticides, atrazine, atrazine desisopropyl, atraton, carboxin, linuron, and chlorpyrifos was studied under equilibrium (batch) conditions. To describe the adsorption capability of the synthesized polymers, Langmuir and Freundlich models were used. The Freundlich model provided a better mathematical approximation of the sorption characteristic for polymers nanofibers. To evaluate the adsorption capacity in the presence of interferents experiments on river water samples spiked with a mixture of six pesticides were also performed. The results obtained for the highest concentration levels investigated, show a greater amount of pesticide adsorbed on molecularly imprinted polymers and non‐imprinted polymers compared to those obtained using commercial stationary phases used as reference.